Advances in Grid and Pervasive Computing Third International Conference, GPC 2008, Kunming, China, May 25-28, 2008. Proceedings - Wu, Song; Yang, Laurence Tianruo; Xu, Tony Li (Theoretical Computer Science and General Issues, 2008)
This book constitutes the refereed proceedings of the Third International Conference on Grid and Pervasive Computing, GPC 2008, held in Kunming, China, in May 2008. The 45 revised full papers presented together with 2 keynote lectures were carefully reviewed and selected from 184 submissions. The papers cover all current issues of grid and pervasive computing and focus on topics such as cluster computing, grid computing, high performance computing, network storage, peer-to-peer computing, pervasive computing, the Semantic Web and the Semantic Grid, and service-oriented computing.